PEMANFAATAN APLIKASI DATA ANALYSIS DALAM MENGETAHUI TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN AKADEMIK PADA STMIKAKADEMI BINA INSANI BEKASI - Petrus Dwi Ananto P; Helenia Touana (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2016)
In activities based on services, the customer satisfaction becomes very important thing to be noted. It is similarly with education. The student’s satisfaction towards academic services could be something that needs to be noted by the college. The measurement of student’s satisfaction level was done by using TERRA attributes (tangible, empathy, reliability, responsiveness, and assurance). The measurement of attributes on student’s satisfaction for tangible attributes are lecture equipment, teaching media, and educational facilities; for empathy attributes is the understanding of the students interest; for reliability attributes are the reliability of lecturers and academic staff; for responsiveness attribute is responsive attitude; and for assurance attribute is the treatment on the students. From all the attributes measured, STMIK-Akademi Bina Insaniagreed of all attributes included in the indicators of satisfaction. This statement proves that the students satisfied with the academic services in STMIK-Akademi Bina Insani. By the total sample is 278 students of STMIK-Akademi Bina Insaniwhich obtained information that the level of academic services at STMIK-Akademi Bina Insani is GOOD.